Colonoscopy findings in CDH1 carriers from a multicenter international study - Arjun Chatterjee; Robert Hüneburg; Qijun Yang; Shannon Morrison; Anna Bettzüge; Tim Marwitz; Stefan Aretz; Isabel Spier; Tim Ripperger; Silke Redler; Mykyta Kachanov; Alexander E. Volk; et al. (Familial Cancer, 2025)
Germline (likely-)pathogenic variants (PV) in CDH1 predispose carriers to hereditary diffuse gastric cancer and lobular breast cancer. Previous studies from the United States suggest CDH1 variant carriers have an increased risk for adenomas or sessile serrated lesions (SSL), yet data linking CDH1 PVs and colorectal neoplasia are scarce. We aimed to investigate colonoscopy findings in CDH1 PVs. Adults carrying a PV/LPV in CDH1 with ≥ 1 colonoscopy between 01/01/2004–12/31/2023 were included. Patients were sourced from the David G. Jagelman Inherited Colorectal Cancer Registries at Cleveland Clinic and the German Consortium for Familial Intestinal Cancer. 103 CDH1 PV carriers were included. Most were female (66%) and white (93.1%). The median age at first colonoscopy was 47 years. The adenoma detection rate (ADR) was 29.4% (95% CI:19.9–41.1%) in the German cohort and 48.6% (95% CI: 33.0-64.4%) in the Cleveland cohort ( p = 0.055) and significantly correlated with age (< 45 years, 13.6% (95% CI: 6.40–26.7%); 45–49 years, 52.4% (95% CI: 32.4–71.7%); ≥50 years, 52.6% (95% CI: 37.3–67.5%); p < 0.001). The ADR in Cleveland was higher than the U.S. average ADR but the difference was not statistically significant (48.6% vs. 35.6%, p = 0.08), and the ADR in the German cohort (29.4%) was similar to the national German average risk screening cohort (31.3% in men, p = 0.84; 20.1% in women, p = 0.08). In our screening cohort with CDH1 PV carriers, we demonstrated an ADR of 13.5% in individuals under 45 years, similar to the ADR in patients aged 25–40 years with a family history of CRC. Overall, SSL detection rate was 9.7%. Colorectal cancer was diagnosed in 3 patients (3.2%), 2/3 with an early age of onset before the age of 50 years. This first international study provides preliminary evidence of a higher ADR in U.S. CDH1 PV carriers compared to the general population, with a high number of adenomas detected before the age of 50. This may indicate an increased CRC risk that should be explored in larger studies.

Validation of GEMS operational v2.0 total column NO2 and HCHO during the GMAP/SIJAQ campaign - Kangho Bae; Chang-Keun Song; Michel Van Roozendael; Andreas Richter; Thomas Wagner; Alexis Merlaud; Gaia Pinardi; Martina M. Friedrich; Caroline Fayt; Ermioni Dimitropoulou; Kezia Lange; Tim Bösch; et al. (Science of The Total Environment, 2025)

Surveillance recommendations for DICER1 pathogenic variant carriers: a report from the SIOPE Host Genome Working Group and CanGene-CanVar Clinical Guideline Working Group - Jette J. Bakhuizen; Helen Hanson; Karin van der Tuin; Fiona Lalloo; Marc Tischkowitz; Karin Wadt; Marjolijn C. J. Jongmans; Beate B. Dörgeloh; Roula A. Farah; Stavros Glentis; Lisa Golmard; Juliane Hoyer; et al. (Familial Cancer, 2021)
DICER1 syndrome is a rare genetic disorder that predisposes to a wide spectrum of tumors. Developing surveillance protocols for this syndrome is challenging because uncertainty exists about the clinical efficacy of surveillance, and appraisal of potential benefits and harms vary. In addition, there is increasing evidence that germline DICER1 pathogenic variants are associated with lower penetrance for cancer than previously assumed. To address these issues and to harmonize DICER1 syndrome surveillance programs within Europe, the Host Genome Working Group of the European branch of the International Society of Pediatric Oncology (SIOPE HGWG) and Clinical Guideline Working Group of the CanGene-CanVar project in the United Kingdom reviewed current surveillance strategies and evaluated additional relevant literature. Consensus was achieved for a new surveillance protocol and information leaflet that informs patients about potential symptoms of DICER1 -associated tumors. The surveillance protocol comprises a minimum program and an extended version for consideration. The key recommendations of the minimum program are: annual clinical examination from birth to age 20 years, six-monthly chest X-ray and renal ultrasound from birth to age 6 years, and thyroid ultrasound every 3 years from age 8 to age 40 years. The surveillance program for consideration comprises additional surveillance procedures, and recommendations for DICER1 pathogenic variant carriers outside the ages of the surveillance interval. Patients have to be supported in choosing the surveillance program that best meets their needs. Prospective evaluation of the efficacy and patient perspectives of proposed surveillance recommendations is required to expand the evidence base for DICER1 surveillance protocols.

Correction to: Choose and stay on one out of two paths: distinction between clinical versus research genetic testing to identify cancer predisposition syndromes among patients with cancer - Tim Ripperger; D. Gareth Evans; David Malkin; Christian P. Kratz (Familial Cancer, 2021)

Effective identification of cancer predisposition syndromes in children with cancer employing a questionnaire - Miriam Schwermer; Astrid Behnert; Beate Dörgeloh; Tim Ripperger; Christian P. Kratz (Familial Cancer, 2021)
Approximately 10% of children with newly diagnosed cancer have a cancer predisposition syndrome (CPS). The optimal diagnostic approach to identify them among children diagnosed with cancer is unknown. Objective : To determine whether the use of a one-page questionnaire can improve the CPS diagnosis among children with an oncologic condition. Design : Comparative effectiveness research. Setting : Referral center for children with cancer. Results : 739 children diagnosed with an oncologic condition between 2012 and 2019. All children with a newly diagnosed oncologic condition presenting to Hannover Medical School between January 1st 2017 and December 31st 2019 were prospectively evaluated with a CPS questionnaire. Children in whom the questionnaire suggested the need of a genetic workup were further evaluated. All children diagnosed with an oncologic condition between January 1st 2012 and December 31st 2016 served as control. The CPS diagnoses established during both time periods were evaluated and compared. A CPS was diagnosed in 27 out of 287 children (9.4%) during the questionnaire period versus 24 out of 452 children (5.3%) during the control period ( P = 0.032). Conclusion : The CPS questionnaire appears to significantly improve the diagnosis of children with CPS among children with a newly diagnosed oncologic condition.

Choose and stay on one out of two paths: distinction between clinical versus research genetic testing to identify cancer predisposition syndromes among patients with cancer - Tim Ripperger; D Gareth Evans; David Malkin; Christian P. Kratz (Familial Cancer, 2021)

Genetic testing and surveillance in infantile myofibromatosis: a report from the SIOPE Host Genome Working Group - Simone Hettmer; Guillaume Dachy; Guido Seitz; Abbas Agaimy; Catriona Duncan; Marjolijn Jongmans; Steffen Hirsch; Iris Kventsel; Uwe Kordes; Ronald R. de Krijger; Markus Metzler; Orli Michaeli; et al. (Familial Cancer, 2021)
Infantile myofibromatosis (IM), which is typically diagnosed in young children, comprises a wide clinical spectrum ranging from inconspicuous solitary soft tissue nodules to multiple disseminated tumors resulting in life-threatening complications. Familial IM follows an autosomal dominant mode of inheritance and is linked to PDGFRB germline variants. Somatic PDGFRB variants were also detected in solitary and multifocal IM lesions. PDGFRB variants associated with IM constitutively activate PDGFRB kinase activity in the absence of its ligand. Germline variants have lower activating capabilities than somatic variants and, thus, require a second cis-acting hit for full receptor activation. Typically, these mutant receptors remain sensitive to tyrosine kinase inhibitors such as imatinib. The SIOPE Host Genome Working Group, consisting of pediatric oncologists, clinical geneticists and scientists, met in January 2020 to discuss recommendations for genetic testing and surveillance for patients who are diagnosed with IM or have a family history of IM/ PDGFRB germline variants. This report provides a brief review of the clinical manifestations and genetics of IM and summarizes our interdisciplinary recommendations.

A novel germline POLE mutation causes an early onset cancer prone syndrome mimicking constitutional mismatch repair deficiency - Katharina Wimmer; Andreas Beilken; Rainer Nustede; Tim Ripperger; Britta Lamottke; Benno Ure; Diana Steinmann; Tanja Reineke-Plaass; Ulrich Lehmann; Johannes Zschocke; Laura Valle; Christine Fauth; et al. (Familial Cancer, 2017)